Measurement of prompt J/ψ and beauty hadron production cross sections at mid-rapidity in pp collisions at √s = 7 TeV - Abelev, Betty; Angelov, Venelin; Constantin, Paul; Grajcarek, Robert; Herrmann, Norbert; Klein, Jochen; Koch, Kathrin; Krawutschke, Tobias; Kweon, MinJung; Lohner, Daniel; Lu, Xianguo; Maire, Antonin; et al. (Journal of high energy physics, 2012)
The ALICE experiment at the LHC has studied J/ψ production at mid-rapidity in pp collisions at s√=7s=7 \sqrt{s}=7 TeV through its electron pair decay on a data sample corresponding to an integrated luminosity L int = 5.6 nb−1. The fraction of J/ψ from the decay of long-lived beauty hadrons was determined for J/ψ candidates with transverse momentum p t 1.3 GeV/c and rapidity |y| 0.9. The cross section for prompt J/ψ mesons, i.e. directly produced J/ψ and prompt decays of heavier charmonium states such as the ψ(2S) and χc resonances, is σprompt J/ψ (p t > 1.3 GeV/c, |y| < 0.9) = 8.3 ± 0.8 (stat.) ± 1.1 (syst.) +1.5−1.4−1.4+1.5 _{-1.4}^{+1.5 } (syst. pol.) μb. The cross section for the production of b-hadrons decaying to J/ψ with p t > 1.3 GeV/c and |y| < 0.9 is σJ/ψ←hBσJ/ψ←hB {σ_{{{J \left/ {{ψ ← {{h}_{B}}}} \right.}}}} (p t > 1.3 GeV/c, |y| < 0.9) = 1.46 ± 0.38 (stat.) +0.26−0.32−0.32+0.26 _{-0.32}^{+0.26 } (syst.) μb. The results are compared to QCD model predictions. The shape of the p t and y distributions of b-quarks predicted by perturbative QCD model calculations are used to extrapolate the measured cross section to derive the bb¯¯¯bb¯ b\overline{b} pair total cross section and dσ/dy at mid-rapidity. Open image in new window
Gesehen am 15.11.2018
The ALICE Collaboration: Betty Abelev, Venelin Anguelov, Paul Constantin, Robert Grajcarek, Norbert Herrmann, Jochen Klein, Kathrin Koch, Tobias Krawutschke, Min Jung Kweon, Daniel Lohner, Xianguo Lu, Antonin Maire, Jorge Mercado Perez, Ken Oyama, Yvonne Chiara Pachmayer, Sylwester Radomski, Rainer Martin Schicker, Kai Oliver Schweda, Johanna Stachel, Johannes Hendrik Stiller, Jochen Ulrich, Sara Vallero, Yifei Wang, Bernd Stefan Windelband, Alice Zimmermann [und weitere]